Quantitative Characterisation Of Complex Porous Phase Via Mathematical Morphology And Fractal Geometry - Teo, Lay Lian (2006)
We address the problem of characterisation of rock porous medium where rock cross sectional data, acquired via microscopic mean, as input, such as sedimentary rock sample. Our starting point is the greyscale microscopic data represented on two-dimensional space.